Salary Provision Policy 13 for Non-State Civil Apparatus Employees (Journal of Politica Governo, 2026)
The provision of the thirteenth salary is mandated by the President of the Republic of Indonesia through Government Regulation of the Republic of Indonesia Number 14 of 2024 concerning the Provision of Religious Holiday Allowances and the Thirteenth Salary for State Officials, Retirees, Pension Beneficiaries, and Allowance Recipients in 2024. This policy aims to maintain public purchasing power and assist in fulfilling the family needs of government employees. However, employees who are not part of the State Civil Service at the Regional Public Hospital of West Nusa Tenggara Province are not included as recipients of the thirteenth salary based on the provisions stipulated in Government Regulations and Governor Regulations. On the other hand, these non-civil service employees perform duties and service functions similar to those of civil servants, which has led to demands for the provision of the thirteenth salary. This study aims to analyze the policy on the provision of the thirteenth salary for non-civil service employees at the Regional Public Hospital of West Nusa Tenggara Province and to identify the obstacles encountered in its implementation. The research employs a normative method with a statutory approach through the analysis of regulations related to the provision of the thirteenth salary and financial management policies within the Regional Public Service Agency system. The results of the study indicate that the implementation of the thirteenth salary for non-civil service employees still faces several major challenges, including the absence of specific regulations governing the provision of the thirteenth salary for non-civil service employees, the lack of budget allocation in the Business and Budget Plan, and the relatively large number of non-civil service employees,  which creates a financial burden for the hospital. Therefore, internal regulations are required as a legal basis, along with adequate budget planning, to support the implementation of this policy.